Thrombin Generation in Preterm Newborns With Intestinal Failure-Associated Liver Disease - Ghirardello, Stefano; Raffaeli, Genny; Scalambrino, Erica; Cortesi, Valeria; Roggero, Paola; Peyvandi, Flora; Mosca, Fabio; Tripodi, Armando (Frontiers in Pediatrics, 2020)
Background and aim. Intestinal failure-associated liver disease (IFALD) affects one-fifth of neonates receiving parenteral nutrition (PN) for more than two weeks. We aimed to define the effect of IFALD on hemostasis of preterm infants. Methods. This is an ancillary analysis of a prospective study aimed at defining coagulation in preterm infants. We included neonates exposed to PN (at least 14 days), in full-enteral feeding. We compared thrombin generation in the presence of thrombomodulin, defined as endogenous thrombin potential-ETP, PT, aPTT between infants with IFALD versus those without (controls), at birth, and after 30 days. IFALD was defined as conjugated bilirubin≥1 mg/dl. Results. We enrolled 92 preterm infants (32 IFALD; 60 controls). Cholestatic patients had a lower birthweight, longer exposure to PN, and longer hospitalization. Infants with IFALD showed longer median PT (12.8-vs-12 sec;p=0.02) and aPTT (39.2-vs-36.5 sec;p=0.04) than controls, with no difference in ETP. Conclusions. Despite prolonged PTs and aPTTs infants with IFALD had similar ETP than those without.